Introduction and validation of the Antisocial Beliefs Scale in a sample of Polish prisoners - Skowroński, Bartłomiej (Frontiers in Psychology, 2022)
Purpose: The goal of this study was to create and validate a brief self-report scale of antisocial beliefs. Methods: The Antisocial Beliefs Scale (ABS), the Buss–Perry Aggression Questionnaire (BPAQ), the Mach-IV, the IVE Questionnaire were administrated to 718 prisoners. Dimensionality and construct validity of the ABS was investigated using CFA techniques, along with confirmatory bifactor analysis and second-order factor analysis. Four alternatives models of the ABS were specified and tested using Mplus (WLSMV estimation). A comparison sample of adult male non-offenders (n = 339) was also recruited. This sample completed only the ABS. Results: The bi-factor model offered the best representation of the data. Results suggest that the ABS consists of eight subscales (physical aggression, lack of empathy, absence of prosocial standards, lack of guilt or remorse, incapacity for mutually intimate relationships, risk taking, egocentrism and manipulativeness). The ABS showed different levels of antisocial beliefs in offenders and non-offenders. The factors of ABS correlate significantly with external variables. The Antisocial Beliefs Scale demonstrated very good internal consistency. Conclusions: The Antisocial Beliefs Scale can be used among participants with criminal history.